Археологія замчищ Західної України: історія та перспективи дослідження - Терський, С. В.; Омельчук, Б. А. (Lviv Polytechnic Publishing House, 2016)
Проаналізовано процес археологічного дослідження замків та замчищ Прикарпаття та Волині. У Західних областях України та на Львівщині, зокрема на це звернено недостатню увагу, хоча зрідка реставраційні роботи в замках поєднані з розкопками. Обґрунтовано висновок про важливу роль археологічних матеріалів для з’ясування багатьох аспектів функціонування замків. The article analyzes the process of archaeological research locks and locks’site Carpathians and Volyn. It was shown the growth of public interest in the preservation and restoration of castles of Western Ukraine. The modern typology attractions. Defined stages of the castle archaeology Ukraine. It is established that XIV–XVI centuries. characteristic of the region are castles type “motte and bailey”. Since the end of the XVI century. become the dominant type of bastion castles. Today mapped locks Carpathians and Volyn conducted targeted saving research in the fortress of the district. Dniester and the castles of Transcarpathia (Nevytske, Hust). The results of the study an important royal castle in sea level. Rakoczi Castle, defending the crossing over the river. Southern Bug 2.5 km east of the castle town Medzhybizh in the floodplain. Southern Bug. Found that in Western Ukraine and Lviv region, including archaeological research of locks so far paid insufficient attention, although occasionally the restoration work in the castles are connected with the excavation. Today, much of medieval castles lost its ground and walls of their study lies entirely in the field of archaeology. Examples detect collections of artifacts in the study of locks. These collections not only provide a more complete picture of the composition and origin of arms castle garrison, but most often the case with customs more fully characterize the trade. Grounded conclusion about the importance of archaeological materials to clarify many aspects of the locks.
Keywords: археологічні знахідки; реставраційні роботи; замки; Львівщина; розкопки; archaeological; restoration work; castles; Lviv; excavations; 902(477.83)